LIVING QUR’AN DALAM TRADISI TINGKEBAN (SYUKURAN TUJUH BULANAN IBU HAMIL) UNTUK MENINGKATKAN NILAI SPIRITUAL MASYARAKAT - Mubarok, Muh Ibnul; M. Rusydi, M. Rusydi (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
The implementation of the Living Qur'an began with the phenomenon of people reading the Koran at certain times and traditions. Apart from that, the Al-Qur'an is always memorized, making pieces of Al-Qur'an verses to decorate mosques and homes. This research is focused and aimed at describing the implementation of the living Quran in the seven-monthly tradition in Ampel Village, Wuluhan District, Jember Regency. The method used in this research is descriptive qualitative research which uses observation, interviews and documentation to collect data. The research results show that the Seven Months Tradition is a procession carried out as a form of gratitude to Allah SWT, for having been blessed with a child. The processions carried out in the Seven Months Tradition include: reading selected surahs. The aim is that the baby in the womb will resemble the Prophet Yusuf and Siti Maryam in terms of appearance, morals and obedience. Apart from that, reading verses from the Al-Qur'an, prayers and tahlil can have an impact on mothers and babies.